Chứng minh:
\(\text{ 2√3(√2-3)+(2-√3)^2+6√3 = 5}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(P=1+3+3^2+...+3^7\)
\(=\left(1+3\right)+...+\left(3^6+3^7\right)\)
\(=1\left(1+3\right)+...+3^6\left(1+3\right)\)
\(=1\cdot4+...+3^6\cdot4\)
\(=4\cdot\left(1+...+3^6\right)⋮4\)
Đpcm
p=1+3+32+33+34+35+36+37
p=(1+3)+(32+33)+(34+35)+(36+37)
p=4.1+(32.1+32.3)+(34.1+34.3)+(36.1+36.3)
p=4.1+32(1+3)+34(1+3)+36(1+3)
p=4.1+32.4+34.4+36.4
p=4.(1+32+34+36)
vay P chia het cho 4
1/ a/ \(\sqrt{\left(6+2\sqrt{5}\right)^3}-\sqrt{\left(6-2\sqrt{5}\right)^3}\)
\(=\sqrt{\left(\sqrt{5}+1\right)^6}-\sqrt{\left(\sqrt{5}-1\right)^6}\)
\(=\left(\sqrt{5}+1\right)^3-\left(\sqrt{5}-1\right)^3\)
\(=32\)
b/ \(\sqrt{\left(3-2\sqrt{2}\right)\left(4-2\sqrt{3}\right)}\)
\(=\sqrt{\left(\sqrt{2}-1\right)^2\left(\sqrt{3}-1\right)^2}\)
\(=\left(\sqrt{2}-1\right)\left(\sqrt{3}-1\right)\)
\(=\sqrt{6}-\sqrt{2}-\sqrt{3}+1\)
Câu 3/ \(A=\sqrt{2+\sqrt{2+\sqrt{2+...+\sqrt{2+\sqrt{2}}}}}\)
\(< \sqrt{2+\sqrt{2+\sqrt{2+...+\sqrt{2+\sqrt{4}}}}}=2\)
Ta lại có:
\(A=\sqrt{2+\sqrt{2+\sqrt{2+...+\sqrt{2+\sqrt{2}}}}}>\sqrt{2}>1\)
\(\Rightarrow1< A< 2\)
Vậy \(A\notin N\)